The Influence of Ease of Use and Product Completeness on Purchasing Decisions on the Lazada Application The Word of Revelation - Qomariyatul Wahyu; Rusminah HS (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of ease of use and product completeness on purchasing decisions in the Lazada application. The rapid development of e-commerce has shifted consumer shopping behavior from conventional transactions to online shopping activities. In this competitive digital era, ease of use and product completeness are considered important factors influencing consumer purchasing decisions. This study uses a quantitative approach with an associative research design. The population of this study consists of consumers in Mataram City who have made purchases through the Lazada application. The sample was determined using the Lemeshow formula, resulting in 100 respondents selected through a purposive sampling technique. Data were collected using an online questionnaire and analyzed using multiple linear regression analysis with IBM SPSS Statistics. The results showed that ease of use has a positive and significant influence on purchasing decisions, indicated by a significance value of 0.000 and a regression coefficient of 0.456. Product completeness also has a positive and significant influence on purchasing decisions, with a significance value of 0.000 and a regression coefficient of 0.422. Together, ease of use and product completeness contribute 64.9% to purchasing decisions. These findings suggest that increasing the app's ease of use and providing a wider variety of products can improve consumer purchasing decisions on e-commerce platforms, particularly Lazada